Coping Stress for Students Who Studying While Working - Hamidah Anzalna Rahmah; Riza Noviana Khoirunnisa (Character Jurnal Penelitian Psikologi, 2023)
This research aims to reveal the description of stress experienced by students who are working and how coping stress is used to overcome the stress. This research uses a qualitative case study approach. There were three participants in this research students who were working. Collecting data using semi-structured interviews with students who were working. Data analysis used is thematic analysis by collecting data and processing it, coding and forming themes. This research succeeded in revealing that the three participants indicated that the stress they experienced was triggered by family pressure, feelings of worry, difficulty managing time and fatigue due to studying while working, this often causes problems to come together. As for coping with stress, students do it in the form of emotion-focused coping by means of selfacceptance, positive interpretation of stress, seeking social emotional support, not refusing to associate religiosity with stress management.